Development of Urea Sensor Based on colorimetric method and Digital RGB Analysis - Fauziyah, Begum; Khoiriyah, Muslimatul; Hakim, Abdul; Wafi, Abdul (International Journal of Engineering and Technology, 2026)
A simple and low cost of urea sensor has been developed using diacetyl monoxime (DAM), Thiosemicarbazide (TSC), Sulfuric Acid and Phosphoric Acid to form pink-azo dye compoud. A urea sensor was manufactured by immobilizing reagents to the silica gel plate. The sensor was tested to determine urea in various concentrations including 0; 5; 6; 25; 26 and 80 mg/dL.  The color formed on the sensor was captured by Samsung camera 12 megapixel in the black box to obtain color digital data such as red, green, blue (RGB). The Δ Mean RGB valuess were 0.0; 51.6; 51.9; 58.5; 61.4 and 75.3 respectively.
Keywords: Colorimetric; kidney; RGB value; sensor; urea